MODEL OF ENGINEERING STUDENTS’ GENERIC SKILLS: CONFIRMATORY FACTOR ANALYSIS - Mokhtar, Seri Bunian; Husain, Mohd Yusof; Rahman, Saemah (Journal of Human Capital Development (JHCD), 2012)
This survey study was carried out to review the generic skills (GS) model for engineering students. A total of 527 respondents were involved in this research. The variables presented in this research were the skill of gathering and analyzing information, communication skill, team working skill, problem solving skill, life long learning skill, technology utilization skill, critis and creative thinking skill, entrepreunuership, leadership and personal qualities. Data were analyzed descriptively for reliability (Cronbach Alpha values) and confirmatory factor analysis (CFA) was used to obtain 10 factor solutions using AMOS software. The results showed that the Cronbach Alpha was on the classification of high and very high which was higher than 0.70. Result of second order CFA confirmed 10 factors solution with data collected was fit with model. The study also proposed a model of generic skills for engineering students. KEYWORDS: generic skills, engineering students, confirmatory factor analysis